DESCRIPTION OF PARENTING STYLES ON ADOLESCENTS WITH RISK BEHAVIOR IN VOCATIONAL HIGH SCHOOL â€œXâ€ PANGANDARAN REGENCY: Gambaran Pola Asuh Orang Tua pada Remaja dengan Perilaku Berisiko di SMKâ€œXâ€ Kabupaten Pangandaran - Alex Setiawan; Neti Juniarti; Fanny Adistie (STIKes Hang Tuah Pekanbaru, 2020)
Adolescence is a vulnerable period of risky behaviors. Properparenng style is needed so that adolescents do not engage inrisky behaviors such as smoking, drinking alcoholic beverages,abusing drugs, and engaging in premarital sexual relaons. Thestudy aimed to describe parenng styles in adolescents with riskbehaviors. This was a descripve quantave research with across-seconal approach. The populaon was parents ofstudents with risk behaviors in a Vocaonal High School totaling213 people. The sampling technique was used as a proporonatestrafied random sampling. The number of samples was 139people. Data collecon was performed by using a QuesonnaireParenng Style and Dimensions instrument which had beentested for validity test with a result (.423-.748)) and reliability test(>.70). The collected data was analyzed by using a univariate test.The result showed that almost half of respondents (38.12%) onsmoker's adolescents and (33.33%) of smokers also drinkeradolescents used authoritarian parenng. Whereas, respondentson adolescents who smoked also drunk alcohol and used drugsand respondents on an adolescent who engages in premarital sexall of the respondents (100%) used permissive parenng. Besidesthat, all of the respondents (100%) used authoritarian parenngon adolescents who engage in premarital sex also smoked andused drugs. Therefore, a proper parenng style is very muchneeded by the parent to be able to minimize the level of riskbehavior occurrence in adolescents. Keywords : Adolescent, family, parenng and risk behavior.